Basal cell carcinoma of the lower eyelid is an actinic-induced cancer: The ABCDE concept to explain the relationship between the invasiveness of basal cell carcinoma and actinic damage - Luiza Abreu Minussi; Felipe Key Sakabe; Roxana Barin; Emily Marcotte; Elvira Barbosa Abreu; Miguel Noel Burnier (The Pan-American Journal of Ophthalmology)
Purpose: Basal cell carcinoma (BCC) originates from the basal cells in the epidermis and is particularly prevalent on the eyelid. Ultraviolet (UV) radiation, a key factor in BCC development, induces fibroblast actinic damage and abnormal elastic fiber deposition, leading to cancer development. This study investigates the relationship between UV radiation and BCC on the lower eyelid by examining the incidence and characteristics of this cancer across diverse geographic regions. Materials and Methods: A cohort of 813 BCC eyelid patients from Canada was analyzed. Tumor locations (lower vs. upper eyelid) were recorded. The histopathological evaluation included 707 lower eyelid BCC cases and 493 benign lesions of the lower eyelid. Actinic damage was graded on a scale of 0–3. The presence of in situ BCC was assessed. Results: Results revealed a consistent trend: 87% of Canadian BCC cases occurred on the lower eyelid. Severe actinic damage was observed in 89% of pathological lesions, with 11% showing moderate damage. In contrast, 93% of benign lesions had no detectable actinic damage, whereas 7% showed mild damage. Notably, no BCC cases were in the in situ phase, indicating advanced disease upon diagnosis. Conclusion: These findings confirm that BCC of the lower eyelid is primarily induced by UV radiation exposure. Actinic damage in fibroblasts leads to DNA alterations in dermal fibroblasts and is the hallmark feature in sclerosing BCC. This highlights the critical role of UV-induced genetic damage in the pathogenesis of lower eyelid BCC, emphasizing the need for preventive strategies.